Influenza hemagglutinin-mediated fusion pores connecting cells to planar membranes: flickering to final expansion (The Rockefeller University Press, 1993)
We have studied the fusion between voltage-clamped planar lipid bilayers and influenza virus infected MDCK cells, adhered to one side of the bilayer, using measurements of electrical admittance and fluorescence. The changes in currents in-phase and 90 degrees out-of- phase with respect to the applied sinusoidal voltage were used to monitor the addition of the cell membrane capacitance to that of the lipid bilayer through a fusion pore connecting the two membranes. When ethidium bromide was included in the solution of the cell-free side of the bilayer, increases in cell fluorescence accompanied tee admittance changes, independently confirming that these changes were due to formation of a fusion pore. Fusion required acidic pH on the cell- containing side and depended on temperature. For fusion to occur, the influenza hemagglutinin (HA) had to be cleaved into HA1 and HA2 subunits. The incorporation of gangliosides into the planar bilayers greatly augmented fusion. Fusion pores developed in four distinct stages after acidification: (a) a pre-pore, electrically quiescent stage; (b) a flickering stage, with 1-2 nS pores opening and closing repetitively; (c) an irreversibly opened stage, in which pore conductances varied between 2 and 100 nS and exhibited diverse kinetics; (d) a fully opened stage, initiated by an instantaneous, time- resolution limited, increase in conductance leveling at approximately 500 nS. The expansion of pores by stages has also been shown to occur during exocytosis in mast cells and fusion of HA-expressing cells and erythrocytes. We conclude that essential features of fusion pores are produced with proteins in just one of the two fusing membranes.